(untitled) (Research, Society and Development, 2023)
At the end of 2019 emerged in Wuhan, Hubei, China, a series of unknown causes of pneumonia cases with clinical presentations very similar to viral pneumonia. Was named “2019 novel coronavírus (2019-nCoV)”. The prone position is indicated to be used early in patients undergoing mechanical ventilation with ARDS and with a severe blood gas alteration. The overall objective of the study was to analyze changes in ventilatory mechanics in patients with COVID-19 who developed ARDS on mechanical ventilation submitted to the prone position. This is an integrative literature review, where the descriptors used “prone position”, “COVID-19” e “intubated patients” with boolean operator “AND” through the SciELO, PubMed and BVS databases Inclusion criteria were: articles in English, Spanish and Portuguese, available in full for free, from 2020 to 2022. Exclusion criteria were those that were duplicates and that dealt with spontaneously breathing patients. 319 articles were found. After the implementation of the criteria and inclusion and exclusion, 17 articles remained in the study. The prone position is an effective maneuver, significantly increasing the PaO2/FiO2 ratio, even after re-supination.